2014
DOI: 10.1074/jbc.m114.554766
|View full text |Cite
|
Sign up to set email alerts
|

Transactivation of the Receptor-tyrosine Kinase Ephrin Receptor A2 Is Required for the Low Molecular Weight Hyaluronan-mediated Angiogenesis That Is implicated in Tumor Progression

Abstract: Background: Hyaluronan (HA)-mediated angiogenesis has been implicated in tumor progression. Results: LMW-HA-mediated transactivation of EphA2 is required for PATJ and Dbs membrane recruitment and subsequent RhoA activation required for angiogenesis. Conclusion: EphA2 plays a crucial role in HA-mediated angiogenesis. Significance: Targeting downstream effectors of LMW-HA could be a useful therapeutic intervention for angiogenesis-associated diseases including various malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
2
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 74 publications
(84 reference statements)
0
26
2
2
Order By: Relevance
“…For example, degradation of high-molecular-weight hyaluronan results in accumulation of excess amounts of LMW-HA, which is proangiogenic. 19 Studies have indicated that impairment of blood vascular barrier could be mediated by LMW-HA and an accelerating vascular metastasis of cancer cells was followed. 20,21 To date, there are no reports regarding how LMW-HA modulates lymphatic endothelial cell junctions or facilitates cancer cell metastasis through lymph vessels.…”
Section: Introductionmentioning
confidence: 99%
“…For example, degradation of high-molecular-weight hyaluronan results in accumulation of excess amounts of LMW-HA, which is proangiogenic. 19 Studies have indicated that impairment of blood vascular barrier could be mediated by LMW-HA and an accelerating vascular metastasis of cancer cells was followed. 20,21 To date, there are no reports regarding how LMW-HA modulates lymphatic endothelial cell junctions or facilitates cancer cell metastasis through lymph vessels.…”
Section: Introductionmentioning
confidence: 99%
“…(e) The defect in the transmigration of the cps1Δ strain is not due to growth inhibition in the endothelial cell culture medium. * p < 0.05, ** p < 0.01, *** p < 0.0001, n/s = not significant the endothelial cell barrier and angiogenesis (Lennon et al, 2014). A recent study found that treating endothelial cells with low molecular weight hyaluronan induced the association of CD44v10 (a variant of CD44) with EphA2 and the concomitant activation of EphA2 via phosphorylation, thus suggesting a cross-talk between EphA2 and CD44 (Lennon et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…The roles of EphA2 and CD44 in promoting the transcellular migration of C. neoformans across the BBB may not be incongruous because it is conceivable that both receptors may work in unison. Indeed, both CD44 and EphA2 have been implicated in regulating the endothelial cell barrier and angiogenesis (Lennon et al, ). A recent study found that treating endothelial cells with low molecular weight hyaluronan induced the association of CD44v10 (a variant of CD44) with EphA2 and the concomitant activation of EphA2 via phosphorylation, thus suggesting a cross‐talk between EphA2 and CD44 (Lennon et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EphA2 belongs to the EphA subclass, and is expressed at a minimal level in epithelial cells (33). There is evidence that high levels of EphA2 promote various aspects of the malignant phenotype, including cell growth, angiogenesis, migration, invasion and survival of cancer cells (34,35). A previous study reported that there is a correlation between EphA2 and high levels of angiogenesis markers, in particular, VEGF expression and MVD counts, in HCC tumorigenesis (36,37).…”
Section: Discussionmentioning
confidence: 99%